الأمن المائي ودور مراقبة الأحواض الجوفية لضمان استدامة مصادر المياه - حسين التلوع (The Libyan Journal of Science, 2024)
Groundwater makes up about 98% of the whole bulk of the water resources available in the State of Libya. The average annual precipitation in this arid and semi-arid region is about 100 mm. Therefore, it is essential to establish a network of monitor wells to track the regional water level fluctuations on a large and extensive scale. Data collected from the network are employed in assessing, enhancing and administering the water resources in a fashion that will secure water sustainability for the future generations. These goals can be achieved through proper planning and management programs for the production wells and protecting the aquifer from pollutants and over pumping which may negatively impact the water qualitatively and quantitatively. Moreover, international indicators are significantly utilized to achieve “the sustainable development goals” (SDG6) to monitor water level and quality in the aquifer. Thus, the data and the subsequent results from the monitor well network are analyzed and combined to prepare comprehensive reports that will determine and shape the water policies for the various sectors as of the calendar year 2017, the monitor well network was comprised of 415 wells scattered on a wide geographic range In Libya. Water level measurements are take regularly on quarterly basis. The collected data are combined and analyzed to prepare detailed and professional. Reports which in turn will be submitted to the proper authorities.